Vitamin D deficiency in children and adolescents with obesity: a meta-analysis - Verônica Indicatti Fiamenghi; Elza Daniel de Mello (Elsevier, 2021)
Objective: To evaluate the prevalence of vitamin D deficiency in obese children and adolescents when compared to eutrophic controls. Methods: Systematic review with meta-analysis covering studies with patients aged 0-18 years old diagnosed with obesity and vitamin D deficiency and control group of eutrophic patients. The studies were retrieved in the PubMed, Embase, and LILACS databases in December 2019. The search used the terms "obesity" in combination with "pediatric population" and "vitamin D". Results: Through the search 3155 articles were retrieved; and after analysis, 20 studies were selected according to the study objectives. A total of 24,600 children and adolescents were included. Through meta-analysis, the relative risk for the association between obesity and vitamin D deficiency in the pediatric population was 1.41 (95% CI: 1.26-1.59) (I² = 89%, p < 0.01). Conclusion: Children and adolescents with obesity have higher risk of vitamin D deficiency.